iTRAQ-based quantitative proteomic analysis of the improved effects of total flavones of Dracocephalum Moldavica L. in chronic mountain sickness - Aihaidan Abudouwayiti (Nature Portfolio, 2021)
Abstract To use isobaric tags for relative and absolute quantification (iTRAQ) technology to study the pathogenesis of chronic mountain sickness (CMS), identify biomarkers for CMS, and investigate the effect of total flavones of Dracocephalum moldavica L. (TFDM) on a rat model of CMS. We simulated high altitude hypobaric hypoxia conditions and generated a rat model of CMS. Following the administration of TFDM, we measured the pulmonary artery pressure and serum levels of hemoglobin (Hb), the hematocrit (Hct), and observed the structure of the pulmonary artery in experimental rats. Furthermore, we applied iTRAQ-labeled quantitative proteomics technology to identify differentially expressed proteins (DEPs) in the serum, performed bioinformatics analysis, and verified the DEPs by immunohistochemistry. Analysis showed that the pulmonary artery pressure, serum levels of Hb, and the Hct, were significantly increased in a rat model of CMS (P < 0.05). Pathological analysis of lung tissue and pulmonary artery tissue showed that the alveolar compartment had obvious hyperplasia and the pulmonary artery degree of muscularization was enhanced. Both pulmonary artery pressure and tissue morphology were improved following the administration of TFDM. We identified 532 DEPs by quantitative proteomics; gene ontology (GO)and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis further revealed that metabolic pathways associated with coagulation and complement play crucial roles in the occurrence of CMS. Immunohistochemistry verified that several DEPs (α-1-acid glycoprotein, collagen, fibulin, haptoglobin, PLTP, and TAGLN2) are important biological markers for CMS. Our analyses demonstrated that TFDM can improve CMS and exert action by influencing the metabolic pathways associated with coagulation and complement. This process relieves pulmonary artery pressure and improves lung function. We also identified that α-1-acid glycoprotein, collagen, fibulin, haptoglobin, PLTP, and TAGLN2 may represent potential biomarkers for CMS.